2016
DOI: 10.1073/pnas.1515091113
|View full text |Cite
|
Sign up to set email alerts
|

Echolocating bats use future-target information for optimal foraging

Abstract: When seeing or listening to an object, we aim our attention toward it. While capturing prey, many animal species focus their visual or acoustic attention toward the prey. However, for multiple prey items, the direction and timing of attention for effective foraging remain unknown. In this study, we adopted both experimental and mathematical methodology with microphone-array measurements and mathematical modeling analysis to quantify the attention of echolocating bats that were repeatedly capturing airborne ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 29 publications
5
54
0
Order By: Relevance
“…During call emission, the animals can variably adjust their sonar beam49 and the echo perception can be influenced through motor behaviors of the head or the pinnae4950. A recent study on insect-eating bats demonstrated that, while hunting, the bats shift their sonar beam and flight path towards the second prey before capturing the immediate prey which increases the capture rate51. In the present study, the effects of attention could not be tested because neuronal recordings were performed in anesthetized bats.…”
Section: Discussionmentioning
confidence: 93%
“…During call emission, the animals can variably adjust their sonar beam49 and the echo perception can be influenced through motor behaviors of the head or the pinnae4950. A recent study on insect-eating bats demonstrated that, while hunting, the bats shift their sonar beam and flight path towards the second prey before capturing the immediate prey which increases the capture rate51. In the present study, the effects of attention could not be tested because neuronal recordings were performed in anesthetized bats.…”
Section: Discussionmentioning
confidence: 93%
“…From our observation, we concluded that these prey are roughly ten times slower than P . abramus (which has an average speed of 5 m/s) and therefore assumed that the movement of the prey, at this study site, was negligible during the brief period of approach and capture (< 3 s) in each flight sequence examined in this study [17]. …”
Section: Methodsmentioning
confidence: 99%
“…We also reported that the bats directed their pulse toward the subsequent target before capturing the immediate one when attacking two successive targets [5]. On the other hand, our recent study adopted a mathematical methodology to estimate parameters representing the flight attention of bats for their measured flight paths during the phase of approaching prey [17]. (Note that the flight attention is derived from a parameter of weighing factors to minimize the angular difference between the bat’s flight direction and the direction to its prey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Saccadic eye movements sequentially sample a visual scene in fast temporal succession by steering the gaze to points of interest and can be used to infer the underlying attentional process (Hayhoe and Ballard, 2005;Henderson, 2003;Yarbus, 1967). Correspondingly, we here evaluated the scanning movements of the biosonar beam of horseshoe bats to infer the bats' sonar attention (Fujioka et al, 2016;Ghose and Moss, 2003;Seibert et al, 2013;Surlykke and Moss, 2000) towards passive acoustic environmental cues.…”
Section: Introductionmentioning
confidence: 99%